Ensuring the Protection of the Rights of the Child is a Priority in the Legislation of Kazakhstan - ZHUMABAYEVA, Zhanar; ZHAMIYEVA, Roza; BALGIMBEKOVA, Gulnara; ARENOVA, Leila; SMAGULOVA, Rizagul (Journal of Advanced Research in Law and Economics, 2019)
Ensuring the rights of the child belongs to the global problems of our time, in the solution of which the entire world community is interested. This is explained by the decisive role of the younger generation in ensuring the viability of society and predicting its future development. However, it should be recognized that no state in the world can claim to be a model in the field of the observance of the rights of the child. Even the most democratic and economically developed countries are characterized by an increase in juvenile delinquency, the presence of families with low living standards, child mortality due to inadequate medical care, and the rise of street children. All these factors prove the impossibility of solving the children's problem only by national means and make it necessary to unite the efforts of the world community as a whole, which led to the emergence of the institution of international legal protection of the rights of the child. International protection of the rights of the child is a system of mutually agreed actions of the state and non-governmental international organizations aimed at developing and ensuring the rights of the child with the goal of creating a full-fledged and harmoniously developed personality, facilitating their incorporation into national legislation and providing international assistance to children of underdeveloped states. At the international level, there are many procedures and mechanisms that directly or indirectly relate to the protection of the rights of the child. However, despite the relatively large number of such bodies, it is their multiplicity that creates certain difficulties for the effective protection of the rights of children.